P276 Influence of vedolizumab on extraintestinal manifestations in Inflammatory Bowel Disease: a nationwide multicenter study of the GETECCU Eneida registry. (27th May 2021) - Pérez Galindo, P; Gisbert, J P; Carrillo-Palau, M; Bertoletti, F; González-Vivó, M; Ferrer, J A; Pajares, R; Merino, O; Castaño, A; Chaparro, M; Calvo, M; Barreiro-de-Acosta, M; et al.
Abstract: Background: Evidence regarding vedolizumab (VDZ) influence on extraintestinal manifestations (EIMs) in inflammatory bowel disease patients (IBD) is scarce. Our aim was to analyze the effectiveness of VDZ in pre-existing EIMs and the occurrence of de novo EIMs during VDZ therapy in IBD. Methods: We performed an observational, multicenter, retrospective cohort study including patients from the Spanish ENEIDA registry promoted by GETECCU. We retrospectively identified 551 patients from 20 centers. The co-primary outcomes were to evaluate the response of EIMs to VDZ and to assess the frequency of de novo EIMs during therapy. Secondary outcomes were to analyze associated factors with EIMs response to VDZ, time from VDZ initiation to occurrence of de novo EIMs and the discontinuation rate of VDZ because of worsening/ de novo EIMs. Response and worsening of IBD and EIMs were defined by clinical and laboratory criteria according to the physician's assessment. Results: The median age of the cohort was 49.7 years (IQR 38-60), 50.8% were female, 50.8% had Crohn's disease and 90.4% had prior biologic exposure (more than 1 biologic drug in 57.9%). At baseline 133 patients (24.1%) had pre-existing EIMs of whom 21 showed more than 1 EIM; 76.7% of EIMs were articular and 31% cutaneous. Regarding 77 patients with active EIMs at baseline, response of EIMs to VDZ at 3 months was observed in 23 (29.9%), worsening in 13 (16.9%) and no change in 41 (53.2%). Response rates for active EIMs were 35.4% for peripheral arthritis (PA), 11.8% for axial arthropathy (AA), 35.7% for cutaneous EIMs and 33.3% for ocular EIMs. Response of IBD at 3 months was the only associated factor with response of EIMs to VDZ (OR=3.72; CI 95% [1.08-12.83]). Among 56 patients with inactive EIMs at baseline, worsening of EIMs was observed in 5 patients after 12 months of VDZ therapy (13.5%) (3 cases of PA and 2 of AA). During follow-up 25 patients (4.5%) developed 27 de novo EIMs (17 cases of PA, 4 of AA, 4 of erythema nodosum, 1 of pyoderma gangrenosum and 1 of episcleritis). Median time from VDZ initiation to onset of de novo EIMs was 244 days (IQR 115-693). Presence of more than 1 pre-existing EIM was the only associated factor with de novo EIM onset during first year of VDZ therapy (OR=14.5; 95% CI [3.3-62]). Worsening of pre-existing EIMs or de novo EIMs was the cause of VDZ discontinuation in 15 patients (5.8% of all patients who discontinued VDZ). Conclusion: VDZ achieved clinical response of active EIMs in nearly a third of patients after 3 months of therapy, being the response of IBD to VDZ the only associated factor. Worsening of inactive EIMs or de novo EIMs during VDZ therapy was infrequent.